Application of Classroom Management Principles and Their Effect on Student Motivation in Elementary School - Nurlita, Juniatul Ana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research is a qualitative descriptive study. The aim is to describe the application of classroom management principles and explain its effect on the learning motivation of grade 1 students at SDN Mangunlegi 01 Batangan. The participants of this study were 14 students and 1 teacher. The data analysis technique used in this research is interactive data analysis. Based on the analysis, it was concluded that classroom management at SDN Mangunlegi 01 Batangan was carried out properly in accordance with the principles of classroom management, namely: teacher attitudes such as enthusiasm, warmth, and intimacy. Challenging learning. Various learning activities. The flexibility of the teacher in every action. Positive instruction to students. Cultivate discipline in students. Through the implementation of classroom management, students become motivated and exhibit behaviors such as: Active in class. Willing to try hard things. Desire to study successfully. I want to start with myself. Persevere in the face of learning difficulties. Pay attention to the teacher. So it can be concluded that the principle of classroom management has an effect on students' learning motivation.